A Shift Pattern of Bacterial Communities Across the Life Stages of the Citrus Red Mite, Panonychus citri - Zhang, Zhen-yu; Ali, Muhammad Waqar; Saqib, Hafiz Sohaib Ahmed; Liu, Sheng-xuan; Yang, Xin; Li, Qin; Zhang, Hongyu (Frontiers in Microbiology, 2020)
As one of the most detrimental citrus pests worldwide, the citrus red mite, Panonychus citri (McGregor), shows extraordinary fecundity, polyphagia, and acaricide resistance, which may be influenced by microbes as other arthropod pests. However, the community structure and physiological function of microbes in P. citri are still largely unknown. Here, the high-throughput sequencing of 16S rDNA amplicons was employed to identify and compare the profile of bacterial communities across the larva, protonymph, deutonymph and adult stages of P. citri. We observed a dominance of phylums Proteobacteria and Firmicutes, and classes α-, γ-, β-Proteobacteria and Bacilli in the bacterial communities across the host lifespan. Based on the dynamic analysis of the bacterial community structure, a significant shift pattern between the immature (larva, protonymph, and deutonymph) and adult stages was observed. Accordingly, among the major families (and corresponding genera), although the relative abundances of Pseudomonadaceae (Pseudomonas), Moraxellaceae (Acinetobacter), and Sphingobacteriaceae (Sphingobacterium) were consistent in larva to deutonymph stages, they were significantly increased to 30.18 ± 8.76% (30.16 ± 8.75%), 20.78 ± 10.86% (18.80 ± 10.84%), and 11.71 ± 5.49% (11.68 ± 5.48%), respectively, in adult stage, which implied the important function of these bacteria on the adults’ physiology. Actually, the functional prediction of bacterial communities and Spearman correlation analysis further confirm that these bacteria had positively correlations with the pathway of “lipid metabolism” (including 8 sublevel pathways) and “metabolism of cofactors and vitamins” (including 5 sublevel pathways), which all only increased in adult stages. In addition, the bacterial communities were eliminated by using broad-spectrum antibiotics, streptomycin, which significantly suppressed the survival and oviposition of P. citri. Overall, we not only confirmed the physiological effects of bacteria community on the vitality and fecundity of adult hosts, but also revealed the shift pattern of bacterial community structures across the life stages and demonstrated the co-enhancements of specific bacterial groups and bacterial functions in nutritional metabolism in P. citri. This study sheds light on basic information about the mutualism between spider mites and bacteria, which may be useful in shaping the next generation of control strategies for spider mite pests, especially P. citri.